PERILAKU OPORTUNISTIK PENYUSUN ANGGARAN - Parwati, Sayu Made; Budiasih, I Gusti Ayu Nyoman; Astika, Ida Bagus Putra (Jurnal Ilmiah Akuntansi dan Bisnis, 2015)
Budgeting behavioral phenomena that includes self-interest and group interest in the allocation of budget expenditures be an interesting to examined by the agency theory.This research was conducted in 9 (nine) Regency/Municipal in Bali by using time series data obtained from the Regency/Municipal APBD from 2010 to 2041. The research results shows that the variable PAD has positive and significance influenced opportunistic behavior budgeting. DAU and SiLPA has positive influence but not significance. Changes the amount of PAD, DAU and SiLPA influence increased budgeting behavior seen from a particular sector expenditure spread of education, health, infrastructure, grant and social assistance. This research suggested that local government can improve infrastructure of local financial management. Future research could add independent variables such as loan that cannot be explore in this research because the limited of data and use questionnaire to measure the perception of budgeting framer.
Keywords: PAD, DAU, SiLPA , Opportunistic Behavior